ANALISIS FAKTOR – FAKTOR PRODUKSI PADI STUDY KASUS OPERASI PANGAN RIAU MAKMUR DI KABUPATEN KAMPAR - Eka Putra; Suardi Tarumun (Indonesian Journal of Agricultural Economics, 2012)
In general, the present research was aimed to investigate how far was the targetachievement and productivity of Riau Prosperous Food Operation in Kampar Regency.The specific objectives were to analyze factors affecting the rice production level andfactors affecting the rice efficiency and allocation level in Kampar Regency. To achievethe objectives, the descriptive analysis, stochastic frontier production functionalanalysis, maximum likelihood estimate (MLE) referred from Cobb=Douglas productionfunction were used. The main results show that the factors affecting the rice productionof Riau Prosperous Food Operations Program were labors, seeds used, the amount ofUrea fertilizer, the amount of SP-36 fertilizer and liquid organic fertilizer.Whereas fornon Riau Prosperous Food Operations, the factors were the labors, the seeds used andthe amount of Urea fertilizer. Allocation for the Non Riau Prosperous Food Operationsprogram receivers was more efficient than those of Riau Prosperous Food Operations.Whereas, the economic efficiency was in contrast to the allocative efficiency. The RiauProsperous Food Operations was more efficient than Non Riau Prosperous FoodOperations. The main problem in the Riau Prosperous Food Operations program wasthe community low interest to cultivate crops, especially local community. RiauProsperous Food Operations prioritizing financial and physical aids were less effectiveto encourage the community in Kampar to cultivate the crops, especially rice, in a longrun. In other words, the programs should prioritize psychological aspects (motivation)of the community about the importance of the food to support the community socio-economic condition.Key words: Riau Prosperous Food Operations, productivity increase, efficiency